Development of Interactive Learning Media Based on Deep Learning of Solar System Materials - Anasika Rahayu; Dian Septi Nur; M. Abdul Roziq Asrori (CV. Media Digital Publikasi Indonesia, 2025)
Development of Interactive Learning Media ‘METTA’ Based on Deep Learning Approach on Solar System Material. This study aims to develop interactive learning media ‘METTA’ (Getting to Know the Solar System) based on Articulate Storyline with a Deep Learning approach on Solar System material for Grade VI at SD Negeri 2 Suruh. The research used the Research and Development (R&D) method with the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The validation results showed that the media was very feasible, with a material expert score of 95.45%, media expert score of 97.2%, and language expert score of 91.7%. The practicality of the media was very high based on the responses of 98.33% of teachers and 83.9% of students. The effectiveness test results showed a significant increase in learning outcomes, with an N-Gain of 0.75 (high category). The METTA media was declared highly valid, practical, and effective.